Razoabilidade em Charles S. Peirce: uma proposta pragmaticista para o crescimento da razão - Silva, Flávio Augusto Queiroz e (2018)
This investigation inquires into the concept of “the growth of concrete reasonableness” in the philosophy of the pragmaticist Charles S. Peirce (1839 – 1914), addressing it as a fundamental idea in his work. As we have understood, the concept is not only important to comprehend Peirce’s philosophy, but it also structures his thought. In other words, we can understand this great, complex and vivid philosophy, as well as the classification of its branches, based on the “growth of concrete reasonableness”. Therefore, we have looked for the bedrocks of this idea in Peircean Phenomenology, Normative Sciences and Metaphysics. We will see that the idea of an incarnated reasonableness in the Universe, active and always growing, leads us directly to the heart of Peirce’s philosophy: pragmaticism, realism and the strong negation of any nominalist, individualistic and dogmatic ideals whatsoever